PENDIDIKAN GIZI MENGGUNAKAN MEDIA BUKU SAKU MENINGKATKAN PENGETAHUAN DAN PRAKTIK KONSUMSI SAYUR DAN BUAH PADA SISWA SEKOLAH DASAR - Fitria Laras Azadirachta; Sri Sumarmi (Media Gizi Indonesia, 2017)
The average consumption of vegetables and fruits in Indonesia is still low. This condition can cause the emergence of nutritional problems in children. The purpose of this study was to determine the effect of nutritional education using pocketbook to increasing knowledge and practice of vegetables and fruits consumption among elementary students. This research was quasy experiment using pre-test post-test control group design. The sample size was 60 students consisting of 20 students of SDN Kandang Tepus I as control group treated with media leaflet and 40 students of SDN Kandang Tepus II as treatment group given the pocketbook. The result of independent t-test in pre-test of booth groups shows that there was no difference in knowledge (p=0.220) and practice (p=0.091) between the two groups. Independent t-test result on post-test also shows was no difference in knowledge (p=0.421) and practice (p=0.810) between the two groups. The result of paired sample t-test of the treatment group showed the average of pre-test and post-test of knowledge score were 31.50 and 66.25 and the practice were 2.58 and 3.08. There were significant difference of knowledge (p=0.000) and practice (p=0.000) before and after being given pocketbook. Wilcoxon sign rank test in the control group showed that leaflet did not affect knowledge (p=0.052) but affect the practice (p=0.001). It can be concluded that use of pocketbook media influence the knowledge and the respondent practice.